Secondary prophylaxis of esophageal variceal treatment: Endoscopic sclerotherapy, band ligation and combined therapy - long-term results - Sedef ÖZDAL KURAN; Dilek OĞUZ; Erkan PARLAK; Mehmet ASİL and Bahattin ÇİÇEK and Mesut KILIÇ and Selçuk DİŞİBEYAZ and; an ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-